2021
DOI: 10.1016/j.psj.2020.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Effects of supplementing cranberry and blueberry pomaces on meat quality and antioxidative capacity in broilers

Abstract: Cranberry and blueberry pomaces are rich in antimicrobial and antioxidant compounds. They have been identified as potential antibiotic alternatives in animal feed, but their antioxidative capacity for maintaining or improving the meat quality in broilers is not well documented. This study was to determine whether cranberry and wild blueberry pomaces in diets could positively influence the broiler meat quality. A total of 3,150 broilers were randomly allotted to 10 dietary treatments with bacitracin methylene d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…The moisture content in lamb meat was similar (Junkuszew et al, 2020;Khal-Azzawi and Albashr, 2022;Lima et al, 2022), lower (Mioč et al, 2007;Meng et al, 2023;Radzik-Rant et al, 2023) or higher than (Romero-Bernal et al, 2017;Liang et al, 2023) other reported researches. The moisture content reported for chicken meat was similar (Silva Frasao et al, 2021;Xu et al, 2021) to the rates found in the study. Since most of the chicken meat offered for commercial consumption in the market is hybrid, it is expected that the data obtained would be uniform.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The moisture content in lamb meat was similar (Junkuszew et al, 2020;Khal-Azzawi and Albashr, 2022;Lima et al, 2022), lower (Mioč et al, 2007;Meng et al, 2023;Radzik-Rant et al, 2023) or higher than (Romero-Bernal et al, 2017;Liang et al, 2023) other reported researches. The moisture content reported for chicken meat was similar (Silva Frasao et al, 2021;Xu et al, 2021) to the rates found in the study. Since most of the chicken meat offered for commercial consumption in the market is hybrid, it is expected that the data obtained would be uniform.…”
Section: Resultssupporting
confidence: 83%
“…While the values reported for sheep were in agreement with (Costa et al, 2009;Romero-Bernal et al, 2017;Radzik-rant et al, 2023) or higher than literature reports and findings (Mioč et al, 2007;Lima et al, 2022;Latoch et al, 2023;Lunesu et al, 2023;Uushona et al, 2023). The rates found for chicken meat were higher than the reported values Xu et al, 2021;Sugiharto et al, 2022;Weng et al, 2022;Fathi et al, 2023). The protein values found for rabbit meat were similar to the results found in the other studies (Belichovska et al, 2017;Frunză et al, 2023;Galeano-Díaz et al, 2023).…”
Section: Figure 2 Ash Content Of Meat Samples Obtained From Different...supporting
confidence: 87%
See 1 more Smart Citation
“…Considering that the fat concentration of WM is eight times higher than CL (Table 2) and the inclusion rate of the two considered feed additives (6% WM vs. 1% or 2% CL), the higher fat deposition in the WM group's breast meat is an expected result. Using cranberry and blueberry pomaces in broiler diets, Xu et al [31] reported no effect of dietary berries on the proximate composition of the breast meat. The abdominal fat of broilers was significantly decreased in an experiment that used dietary sumac berries leading to reduced low-density lipoproteins in the blood.…”
Section: Proximate Composition Of Breast Tissuementioning
confidence: 99%
“…(coccidiosis), to stimulate the growth of cecal beneficial bacteria, and to influence lipid and serum enzyme levels in broiler chickens [ 14 , 15 ]. Dietary cranberry and lowbush blueberry pomaces in feeds could also improve the quality and antioxidant capacity of chicken meat [ 16 ]. Limited studies have investigated the mechanisms behind the ability of these berry pomaces to modulate gut microbiome and host metabolism in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%